Reshaping the Food System for Ecological Public Health - Lang, Tim (Taylor & Francis, 2009)
Twenty-first-century food policy will have to address a new set of fundamentals. Some are relatively new such as climate change and peak oil, and some merely new versions of very old ones such as water, population, land pressures, labor, and urbanisation. Policy-makers now need radically to alter the policy mix inherited from the last major policy reconfiguration in the mid-20th century. Then the demon was supply, and poor health was mainly due to underconsumption and poverty. The policy solution was to raise output and reduce prices. Today the challenge is more complex, a coexistence of over-, under-, and malconsumption alongside continuing gross inequalities within and between nations. The article proposes that a new paradigm is emerging, termed here ecological public health, which sees human and planetary health as linked and food as a key connection point. The article outlines aspects of what this entails, stressing the need for food policy to address not just supply but governance and consumer cultural challenges too. Seven priorities are proposed for policy-makers.